Answer:
Simplify
![Q-[R+S]-T](https://tex.z-dn.net/?f=Q-%5BR%2BS%5D-T)
The answer is:
![10m+5n-24](https://tex.z-dn.net/?f=10m%2B5n-24)
Step-by-step explanation:
We have the expressions:
![Q=7m+3n\\R=11-2m\\S=n+5\\T=-m-3n+8](https://tex.z-dn.net/?f=Q%3D7m%2B3n%5C%5CR%3D11-2m%5C%5CS%3Dn%2B5%5C%5CT%3D-m-3n%2B8)
Now, we need simplify:
![Q-[R+S]-T](https://tex.z-dn.net/?f=Q-%5BR%2BS%5D-T)
We need to replace each term by the expressions:
![7m+3n-[(11-2m)+(n+5)]-(-m-3n+8)](https://tex.z-dn.net/?f=7m%2B3n-%5B%2811-2m%29%2B%28n%2B5%29%5D-%28-m-3n%2B8%29)
We need to remember the rule of signs:
![-/-=+](https://tex.z-dn.net/?f=-%2F-%3D%2B)
![-/+=-](https://tex.z-dn.net/?f=-%2F%2B%3D-)
![+/+=+](https://tex.z-dn.net/?f=%2B%2F%2B%3D%2B)
With this in mind we solve the parentheses:
![7m+3n-[(11-2m)+(n+5)]-(-m-3n+8)](https://tex.z-dn.net/?f=7m%2B3n-%5B%2811-2m%29%2B%28n%2B5%29%5D-%28-m-3n%2B8%29)
![7m+3n-[11-2m+n+5]+m+3n-8](https://tex.z-dn.net/?f=7m%2B3n-%5B11-2m%2Bn%2B5%5D%2Bm%2B3n-8)
![7m+3n-11+2m-n-5+m+3n-8](https://tex.z-dn.net/?f=7m%2B3n-11%2B2m-n-5%2Bm%2B3n-8)
let's group common terms
![7m+3n-11+2m-n-5+m+3n-8\\7m+2m+m+3n-n+3n-11-5-8](https://tex.z-dn.net/?f=7m%2B3n-11%2B2m-n-5%2Bm%2B3n-8%5C%5C7m%2B2m%2Bm%2B3n-n%2B3n-11-5-8)
We must add and subtract common terms:
![7m+2m+m+3n-n+3n-11-5-8\\10m+5n-24](https://tex.z-dn.net/?f=7m%2B2m%2Bm%2B3n-n%2B3n-11-5-8%5C%5C10m%2B5n-24)
The answer is:
![10m+5n-24](https://tex.z-dn.net/?f=10m%2B5n-24)
It is B.
The underlined ≥ symbols a closed circle, and any number bigger than 3 if you multiply it with 4 and solve the equation, your answer would be reasonable
Step-by-step explanation:
no
if X=1/7
then
7x=1
...........